Occupational exposure to organic solvents and risk of male breast cancer: a European multicenter case-control study - Nasser Laouali; Corinne Pilorget; Diane Cyr; Monica Neri; Linda Kaerlev; Svend Sabroe; Giuseppe Gorini; Lorenzo Richiardi; Maria Morales-; Agustin Llopis-Gonzalez; Wolfgang Ahrens; Karl-Heinz Jöckel; et al. (Nordic Association of Occupational Safety and Health (NOROSH), 2018)
OBJECTIVES: The etiology of male breast cancer (MBC) is largely unknown but a causal role of exposure to organic solvents has been suggested. Previous studies on occupational risk factors of breast cancer were often restricted to women who are frequently exposed to lower levels and at a lower frequency than men. We investigated the association between MBC and occupational exposure to petroleum and oxygenated and chlorinated solvents in a multicenter case-control study of rare cancers in Europe. METHODS: The study included 104 MBC cases and 1901 controls. Detailed lifetime work history was obtained during interviews, together with sociodemographic characteristics, medical history and lifestyle factors. Occupational exposures to solvents were estimated from a job-exposure matrix. Odds ratios (OR) and their 95% confidence intervals (CI) were calculated using unconditional logistic regression models. RESULTS: Lifetime cumulative exposure to trichloroethylene >23.9 ppm years was associated with an increased MBC risk, compared to non-exposure [OR (95% CI): 2.1 (1.2-4.0); P trend <0.01). This increase in risk persisted when only exposures that occurred ≥10 years before diagnosis were considered. In addition, a possible role for benzene and ethylene glycol in MBC risk was suggested, but no exposure-response trend was observed. CONCLUSIONS: These findings add to the evidence of an increased risk of breast cancer among men professionally exposed to trichloroethylene and possibly to benzene or ethylene glycol. Further studies should be conducted in populations with high level of exposure to confirm our results.